2013
DOI: 10.1038/nature12129
|View full text |Cite
|
Sign up to set email alerts
|

Long-term warming restructures Arctic tundra without changing net soil carbon storage

Abstract: High latitudes contain nearly half of global soil carbon, prompting interest in understanding how the Arctic terrestrial carbon balance will respond to rising temperatures. Low temperatures suppress the activity of soil biota, retarding decomposition and nitrogen release, which limits plant and microbial growth. Warming initially accelerates decomposition, increasing nitrogen availability, productivity and woody-plant dominance. However, these responses may be transitory, because coupled abiotic-biotic feedbac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
354
3
2

Year Published

2015
2015
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 385 publications
(386 citation statements)
references
References 36 publications
27
354
3
2
Order By: Relevance
“…In line with our findings, many experimental warming studies showed increased aboveground productivity (Rustad et al 2001;Hudson, Henry & Cornwell 2011;Melillo et al 2011;Sistla et al 2013). However, only very few studies report effects on biomass partitioning between shoots and roots, and even less is known about the partitioning of recent C assimilates.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In line with our findings, many experimental warming studies showed increased aboveground productivity (Rustad et al 2001;Hudson, Henry & Cornwell 2011;Melillo et al 2011;Sistla et al 2013). However, only very few studies report effects on biomass partitioning between shoots and roots, and even less is known about the partitioning of recent C assimilates.…”
Section: Discussionsupporting
confidence: 77%
“…for almost one growing season. In the longer term, warming effects on C dynamics will also depend on factors we did not investigate, including aboveground biomass turnover and changes in vegetation composition (Walker et al 2006;Myers-Smith et al 2011;Sistla et al 2013;Hagedorn et al 2014). Our experiment suggests that rhizodeposition did not increase with warming, despite increased net 14 C assimilation.…”
Section: Discussionmentioning
confidence: 62%
“…Laboratory experiments offer precise control but lack the in situ nature of field manipulations (Sistla et al, 2013), raising uncertainties as to what degree their results can be extrapolated. Soils isolated during incubation may, for example, underestimate temperature sensitivity of respiration (Podrebarac et al, 2016) or exhibit lag effects .…”
Section: Limitations and Weaknessesmentioning
confidence: 99%
“…Most previous studies have focused on surface soils or permafrost soils, neglecting deep active-layer soils that were identified as subject to strong effects from a 2-decade warming experiment in the Alaskan Arctic (Sistla et al, 2013). Such deeper soils have particular characteristics distinguishing them from both shallow active-layer soils and underlying permafrost: they are most affected by interannual variability in thaw depth, potentially flipping the C source-sink status of entire ecosystems (Goulden et al, 1998;Harden et al, 2012); they are subject to distinctive freeze-thaw, cryoturbation, and microbial dynamics, which are likely to change their sensitivity to climate change and feedback potential (Schuur et al, 2008); and they are known to pose particular problems for accurate modeling of high-latitude carbon dynamics (Nicolsky et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Longer growing seasons, elevated CO2, and increased nutrients released from decomposing organic carbon may all stimulate plant growth [74] to increase C assimilation. Temperature-driven increases in soil respiration would likely be pronounced in the drained mid-boreal uplands where Q 10 values are the largest.…”
Section: Implicatiuons Of Changing Climatementioning
confidence: 99%